The Effectiveness Of The Mim-Mem Method In Mastering Arabic Vocabulary At Muhammadiyah High School 3 Makassar - Nurjannah Nurjannah; Muhram Muhram; Nurtaqwa Amin (Sean Institute, 2024)
This study aims to assess the effectiveness of the Mim-Mem learning method in enhancing Arabic vocabulary mastery (mufradat) and the suitability of the competency standards and indicators set to improve communication skills. The research employs a descriptive qualitative approach with classroom action research. The Mim-Mem method (Mimicry Memorization) focuses on communicative learning that actively involves students in practicing Arabic directly as a second language, emphasizing imitation and memorization exercises. The application of the Mim-Mem method in improving mufradat mastery aims to achieve learning competencies covering mastering mufradat as material for active and effective interaction, fluently mentioning mufradat correctly, and expanding Arabic vocabulary. This method is systematically illustrated in the lesson plan, starting from introduction, core, to closing activities. In its implementation, there is innovation in learning that assists students in Arabic vocabulary pronunciation and articulation, fostering active engagement in the learning process. The effectiveness of the Mim-Mem Method in mufradat learning is reflected in a significant improvement in students' skills in mastering Arabic mufradat vocabulary. Before treatment with the Mim-Mem method, the Arabic vocabulary mastery of class X students at SMK Muhammadiyah 3 Makassar was categorized as less capable because it was below 56% to 75%, specifically at 44.11%. However, after treatment with the Mimicry memorization method, the value increased to 76.47%, categorizing it as effective.